The current state of pediatric drug‐induced sleep endoscopy. (16th June 2016) - Friedman, Norman R.; Parikh, Sanjay R.; Ishman, Stacey L.; Ruiz, Amanda G.; El‐Hakim, Hamdy; Ulualp, Seckin O.; Wootten, Christopher T.; Koltai, Peter J.; Chan, Dylan K.
Abstract : Objectives/Hypothesis: The purpose of this investigation was to assess current drug‐induced sleep endoscopy (DISE) practice patterns at centers that have published on the technique, to identify areas of agreement, and to identify areas of disagreement that may represent opportunities for improvement and standardization. Study Design: Multi‐institutional survey. Methods: A survey was designed in two phases to evaluate preoperative assessment, intraoperative performance, and postoperative management of patients undergoing DISE. The survey was constructed iteratively in consultation with the all of the coauthors, each selected as an expert owing to their previous publication of one or more articles pertaining to pediatric DISE. In the first phase of survey creation, each expert was asked to provide narrative answers to questions pertaining to DISE. These responses served as the basis for a second survey. This second survey was then administered to all pediatric otolaryngologists at each respective institution. Results: Overall, there was a low rate of agreement (33%) among the respondents; however, there was substantial agreement within institution, particularly for the use of anesthetic medications, the use of cine magnetic resonance imaging, and performance of bronchoscopy along with DISE. There was strong agreement among all respondents for performing DISE in a child with severe obstructive sleep apnea following adenotonsillectomy, regardless of comorbidities. Conclusion: This multi‐institutional survey demonstrated a lack of consensus between experts and multiple opportunities for improvement. In general, there was agreement regarding the workup prior to DISE performance and the endoscopic protocol but disagreement regarding anesthetic protocol and management decisions. Level of Evidence: 4. Laryngoscope, 127:266–272, 2017